Pengaruh Work Life Balance, Budaya Organisasi dan Motivasi terhadap Kinerja Karyawan PT. Swadaya Graha Rembang - Mu'arifah, Nurul; Lukiarti, Ming Ming (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2025)
Employee performance is very important to achieve a knowledge based and competitive economy. The form of business and company to improve employee performance is by strengthening work life balance, organizational culture and increasing motivation. Related to this, it is necessarary to conduct research on work life balance, organizational culture and motivation in order to improve employee performance. The research that has been conducted aims to obtain evidence and analysis of the correlation between work life balance, organizational culture and motivation on employee performance. The data collection technique used is the questionnaire method. The data testing, while the data analysis technique uses reliability testing and validity testing, while the data analysis technique uses multiple linier regression analysis using the R² test. The variabel measurement technique uses a likert scale. The population in this study were all employees of PT. Swadaya Graha Rembang totaling 95 employees. The type of data used is subject data. From the results of the study it as known that work life balance has a significant positive effect on performance, organizational culture has a significant positive effect on performance and motivation has a positive but insignificant effect on performance. The results of the determination test show that the variables of work life balance, organizational culture and motivation can explain employee performance by 20,1 %.